2021
DOI: 10.3390/rs13030481
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method Combining ANN and 1D-Var for the Retrieval of Atmospheric Temperature Profiles from FY-4A/GIIRS Hyperspectral Data

Abstract: In our study, a retrieval method of temperature profiles is proposed which combines an improved one-dimensional variational algorithm (1D-Var) and artificial neural network algorithm (ANN), using FY-4A/GIIRS (Geosynchronous Interferometric Infrared Sounder) infrared hyperspectral data. First, according to the characteristics of the FY-4A/GIIRS observation data using the conventional 1D-Var, we introduced channel blacklists and discarded the channels that have a large negative impact on retrieval, then used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Retrieving atmospheric temperature profiles from satellite remote sensing data is crucial for numerical weather prediction (NWP)-based forecasting and climate research [1]. With the development of hyperspectral infrared (IR) sounders with thousands of narrow spectral channels [2], high-spatial-resolution vertical detection of the atmosphere can be achieved [3][4][5]. The hyperspectral IR sounder is capable of sensing changes in thermodynamic variables and tracing gas species as well as critical climate variables [6], and has shown a significant positive impact on global numerical weather prediction (NWP) applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieving atmospheric temperature profiles from satellite remote sensing data is crucial for numerical weather prediction (NWP)-based forecasting and climate research [1]. With the development of hyperspectral infrared (IR) sounders with thousands of narrow spectral channels [2], high-spatial-resolution vertical detection of the atmosphere can be achieved [3][4][5]. The hyperspectral IR sounder is capable of sensing changes in thermodynamic variables and tracing gas species as well as critical climate variables [6], and has shown a significant positive impact on global numerical weather prediction (NWP) applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [40] retrieved atmospheric temperature and humidity profiles based on ANN using the GIIRS hyperspectral data, and achieved good results. Huang et al [4] used 1D-Var and ANN to retrieve atmospheric temperature profiles from the GIIRS hyperspectral data. The results showed that using ANN yields higher accuracy than using 1D-Var in the pressure range of 800-1000 hPa.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the channel centers and Instrumental Spectral Response Functions (ISRFs) of the FY‐4A/GIIRS and FY‐4B/GIIRS are identical for the same wave number channels. The observations from the FY‐4A/GIIRS and FY‐4B/GIIRS can be used for the retrieval of three‐dimensional atmospheric temperature and humidity fields (Huang et al ., 2021), the data assimilation for the numerical weather prediction (Yin et al ., 2021), and the monitoring of trace gases like ammonia (NH 3 ) (Clarisse et al ., 2021). Moreover, the European Meteorological Satellite (EUMESAT) plans to launch their next generation of geostationary satellites in 2024, that is, the Meteosat Third Generation's Sounding satellites (MTG‐S).…”
Section: Introductionmentioning
confidence: 99%
“…The fine spectral resolution of images is obtained through remote sensing sensors which utilize multiple adjacent narrow spectral bands to construct an HSI image [3]. Hyperspectral sensors generate wavelength bands in the visible and infrared spectra [4,5] and analyzing these spectral bands will provide target information in a better manner [6]. The HSI image pixels are composed of electromagnetic radiation bands [7] and hypercubes are used to represent the HSI in three dimensions.…”
Section: Introductionmentioning
confidence: 99%